Analisis Faktor Yang Mempengaruhi Permintaan Ayam Ras Pedaging di Kota Makassar - Meltyn, Maria Mediatrix Masny; Rahim, Abd.; Samsir, Andi; Kamaruddin, Citra Ayni; Hastuti, Diah Retno Dwi (Jurnal EMT KITA, 2024)
This study aims to determine the factors that influence the demand for broiler chicken in the city of Makassar. The sampling method in this study used a purposive sampling method with a sample size of 100 respondents. The results showed that the variable price of broiler chicken, price of fish, number of family members and consumer income simultaneously had an influence on the demand for broiler chicken in Makassar City and partially, the variable price of broiler chicken, number of family members and consumer income has an influence on the demand for broiler chicken in Makassar City.